1-(Furan-2-yl)-2-(2H-indazol-2-yl)ethanone - Özden Özel Güven; Gökhan Türk; Philip D. F. Adler; Simon J. Coles; Tuncer Hökelek (Acta Crystallographica Section E, 2014)
The asymmetric unit of the title compound, C13H10N2O2, contains two crystallographically independent molecules (A and B). The indazole ring systems are approximately planar [maximum deviations = 0.0037 (15) and −0.0198 (15) Å], and their mean planes are oriented at 80.10 (5) and 65.97 (4)° with respect to the furan rings in molecules A and B, respectively. In the crystal, pairs of C—H...N hydrogen bonds link the B molecules, forming inversion dimers. These dimers are bridged by the A molecules via C—H...O hydrogen bonds, forming sheets parallel to (011). There are also C—H...π interactions present, and π–π interactions between neighbouring furan and the indazole rings [centroid–centroid distance = 3.8708 (9) Å] of inversion-related molecules, forming a three-dimensional structure.